Rescue and multiplication of native fruits at the Núleo Luta Camponesa for Agroecology - Silva, Rodrigo Ozelame da; Perez-Cassarino, Julian; Steenbock, Walter (Agrociencia Uruguay, 2022)
This research aims to identify the main multiplication strategies of native tree species in the Atlantic Forest biome, or simply native fruits, and to propose a way to stimulate their promotion. The audience was made up of six groups of farmers from the Núcleo Luta Camponesa of the Ecovida Agroecology Network, located in the south-central region of the State of Paraná-BR. The methodological procedures used the principles of action research and consisted of four complementary phases. The first sought to problematize the importance of native fruits and choose priority species, while the second focused, in a participatory manner, on characterizing the socio-environmental aspects of priority native fruits. Outstanding results are the identification of agroforestry systems as the best strategy for multiplication in the researched context, as well as the elaboration of a guide that can support the rescue and multiplication of such species in other territories. This guide is based on the following sequence: i) rescue looks for native fruits; ii) from what exists in agroecosystems; iii) exchange seeds and seedlings with farmers from other contexts; iv) plant in landscapes that farmers manage.